Analisis Variasi Parameter Backpropagation Artificial Neural Network dan Principal Component Analysis Terhadap Sistem Pengenalan Wajah - Ikhwannul Kholis; Syah Alam (ELECTRANS, 2016)
Face recognition can be done by using Backpropagation Artificial Neural Network (ANN) and Principal Component Analysis (PCA). ANN is made to resemble the human neural system. By varying some parameters on backpropagation, backpropagation characteristics is known to minimize errors and epoch and enlarge Recognition Rate. The experimental results show the relationship between the parameters of eigenvalues, alpha, and coefficient of momentum, against the recognition rate obtained.